Poverty, inequality and evaluation changing perspectives - Fernandez, Ana Maria 1944-; Martin, Frederic P.; Rist, Ray C. (World Bank Group, 2015)
Why monitoring and evaluation capacity development is critical to understanding and addressing issues of poverty and inequality / Robert Lahey -- Managing to reduce inequality : does the changing aidscape and the need to reduce inequality require a new approach to managing aid? / Tom Ling -- Implications of moving from poverty reduction to inequality reduction for evaluation -- Bringing inequality back form the cold : towards a progressive evaluation model / Robert Picciotto -- Conclusion / Frederic P. Martin and Ana-Maria Fernandez
Includes bibliographical references and index
Keywords: Equality; Poverty -- Evaluation; Income distribution